(untitled) (International Journal of Nursing Education, 2021)
Introduction: Diabetes mellitus is a chronic disorder that is increasing rapidly worldwide. Appropriate management of this chronic disease can improve patient’s quality of life, increase life expectancy and relieve society of the huge financial burden. Purpose: The aim of this study was to measure the quality of life of patients with type 2 diabetes and to investigate the role of rehabilitation. Methodology: Data were collected with the use of a questionnaire that consisted of three (3) sections: The Short Form 36 Health Survey Questionnaire, (17) questions adapted from the Diabetes Satisfaction Questionnaire (DTSQs) and the Problem Areas In Diabetes (PAID) scale and questions regarding medical data and demographic information. The sample included a total of n = 122 individuals suffering from type 2 diabetes. The research was carried out in outpatient clinics of two general hospitals and private practices within the region of Western Greece. The results of the study were analyzed using the statistical program SPSS v.25.0. Results: Age and the existence of another health problem besides diabetes have a negative impact on the quality of life of these patients on their physical and emotional health. As patients age, their quality of life decreases affecting all eight scales of the SF-36 Questionnaire. In contrast, patients who had several hours of professional work managed to have a positive outcome on all eight scales. Regarding these patient’s rehabilitation, the results showed that the more satisfied the patients were regarding their treatment plan, doctor and nursing staff, their family’s support, and their diabetic diet, the grater their functionality on all scales. Conclusions: The results showed that it is important for patients with type 2 diabetes to have an active professional life and follow an appropriate rehabilitation program, in order to improve their quality of life.